Falling in love - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2015)
Attending a performance by a opera star he saved in Death at La Fenice, Brunetti learns that the singer is being stalked by an obsessed fan who subsequently attacks a fellow performer.